1977
DOI: 10.1111/j.1744-7348.1977.tb01815.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of silver scurf (Helminthosporium solani) disease of potato with benomyl and thiabendazole

Abstract: SUMMARY Benomyl and thiabendazole, applied as dusts to seed potatoes before chitting (sprouting), reduced the incidence of silver scurf disease on the progeny at lifting and during subsequent storage. Treatment of seed tubers 4 months prior to planting almost completely suppressed sporulation during storage, even under conditions very favourable for the growth of the fungus. The fungicides appeared not to act systemically because developing tubers grown from treated seed were just as susceptible to infection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The results confirm that seed tubers with very little inoculum can be produced by the stem-cutting system or if treated with benomyl, which reduces sporulation (Hirst et al, 1970). However, contamination of untreated stocks with H. solani occurs very rapidly (Jellis and Taylor, 1977), so that repeated chemical treatment would be necessary to prevent a build-up of the disease in initally healthy stocks.…”
Section: Discussionmentioning
confidence: 99%
“…The results confirm that seed tubers with very little inoculum can be produced by the stem-cutting system or if treated with benomyl, which reduces sporulation (Hirst et al, 1970). However, contamination of untreated stocks with H. solani occurs very rapidly (Jellis and Taylor, 1977), so that repeated chemical treatment would be necessary to prevent a build-up of the disease in initally healthy stocks.…”
Section: Discussionmentioning
confidence: 99%
“…can be controlled by applying this fungicide to tubers immediately after harvest and such treatment prevents spread of lesions during storage. The disease is also controlled in ware crops by treating seed tubers; this inhibits production and release of conidia after planting and so prevents the infection of progeny tubers (Jellis & Taylor, 1977), However, the efficacy of both control methods is dependent on the amount and uniformity of thiabendazole deposits on the tubers (Cayley et ai, 1979(Cayley et ai, , 1987 and lack of disease control can often be attributed to poor application.…”
Section: Introductionmentioning
confidence: 99%
“…Hughes respectively, are surface-blemishing diseases spoiling the appearance of potato tubers (Mooi, 1968: Read & Hide, 1984: Langerfeld, 1985. Infection not only results in the downgrading of consignments destined for the consumer market (Hunger & McIntyre, 1979), but also incurs losses in seed production where only limited infection is allowed on certified seed, Silver scurf on tubers can be reduced by treating seed with fungicides like benomyl, thiabendazole (TBZ), imazalil, propiconazole and prochloraz (Jellis & Taylor, 1977b: Cayley et al, 1983: Hide et al, 1987, 1994, although development of tolerance to benzimidazoles by the pathogen limits the usefulness of the first two compounds. By contrast, black dot responds less readily to chemical treatment (Jellis & Taylor, 1977b: Hide et al, 1987, and has been observed to increase following treatment of tubers with benomyl, TBZ or imazalil applied to control silver scurf (Jellis, 1972: Jellis & Taylor, 1977b: Hide et al, 1994.…”
Section: Introductionmentioning
confidence: 99%
“…Infection not only results in the downgrading of consignments destined for the consumer market (Hunger & McIntyre, 1979), but also incurs losses in seed production where only limited infection is allowed on certified seed, Silver scurf on tubers can be reduced by treating seed with fungicides like benomyl, thiabendazole (TBZ), imazalil, propiconazole and prochloraz (Jellis & Taylor, 1977b: Cayley et al, 1983: Hide et al, 1987, 1994, although development of tolerance to benzimidazoles by the pathogen limits the usefulness of the first two compounds. By contrast, black dot responds less readily to chemical treatment (Jellis & Taylor, 1977b: Hide et al, 1987, and has been observed to increase following treatment of tubers with benomyl, TBZ or imazalil applied to control silver scurf (Jellis, 1972: Jellis & Taylor, 1977b: Hide et al, 1994. Of the fungicides previously reported effective against silver scurf, prochloraz appears to have the most pronounced inhibitory activity on growth (but not spore germination) of C. coccodes (Marais, 1990: Read & Hide, 1995, although the latter authors found it less effective for field control of black dot and silver scurf than fenpiclonil.…”
Section: Introductionmentioning
confidence: 99%